Client care strategies, stressors, and solutions in frontline anti‐trafficking work. Issue 2 (2nd December 2020) - Schwarz, Corinne
Abstract: Anti‐human trafficking efforts are increasingly folded into normative frontline work sectors. Service providers must expand their understanding of clients to include the needs of exploited or trafficked persons, even though they may not receive a commensurate increase in training or resources to accommodate these new cases. Using semi‐structured interviews with 54 service providers in the US Midwest, this paper argues that frontline workers move beyond "traditional" emotional labor to labor inflected with forms of crisis, dirty, edge, or extreme work when confronted with trafficking. The specific needs of trafficked clients require the utilization of normatively gendered client care practices: listening, empathizing, performing appropriate responses to clients' emotional displays. However, new or compounding stressors may emerge alongside these new service populations. In order to ethically provide services without risking increased burnout, street‐level bureaucracies must invest in resources for frontline workers to invest in their own emotional well‐being.